The development of new remote technologies in disaster medicine education: A scoping review - Kao, Chia-Lung; Chien, Li-Chien; Wang, Mei-Chin; Tang, Jing-Shia; Huang, Po-Chang; Chuang, Chia-Chang; Shih, Chung-Liang (Frontiers in Public Health, 2023)
Background: Remote teaching and online learning have significantly changed the responsiveness and accessibility after the COVID-19 pandemic. Disaster medicine (DM) has gained prominence as a critical issue recently due to the high frequency of worldwide disasters, especially in 2021. The new artificial intelligence (AI)-enhanced technologies and concepts have recently progressed in DM education. Objectives: The goal of this paper aims is to familiarize the reader with the remote technologies that have been developed and used in DM education over the past 20 years. Literature Scoping Reviews: Mobile edge computing (MEC), unmanned aerial vehicles (UAVs)/drones, deep learning (DL), and visual reality stimulation, e.g., head-mounted display (HMD), are selected as promising and inspiring designs in DM education. Methods: A comprehensive review of the literature on the remote technologies applied in DM pedagogy for medical, nursing, social worker, as well as other health discipline students, e.g., paramedics, were included. Databases including PubMed (MEDLINE), ISI Web of Science (WOS), EBSCO (EBSCO Essentials), Embase (EMB), and Scopus were used. The sourced results were recorded in a Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flowchart and followed in accordance with the PRISMA extension Scoping Review checklist. We included peer-reviewed articles, Epubs (electronic publications such as databases), and proceedings written in English. VOSviewer for related keywords extracted from review articles presented as a tabular summary to demonstrate their occurrence and connections among these DM education articles from 2000 to 2022. Results: A total of 1,080 research articles on remote technologies in DM were initially reviewed. After exclusion, 64 articles were included in our review. Emergency remote teaching/learning education, remote learning, online learning/teaching, and blended learning are those high number of occurrence keywords. As new remote technologies used in emergencies become more advanced, DM pedagogy is facing more complex problems. Discussions: AI-enhanced remote technologies promote learning incentives for medical undergraduate students or graduate professionals, but the efficacy of learning quality remain uncertain. More blended AI-modulating pedagogies in DM education could be increasing important in the future. More sophisticated evaluation and assessment are needed to implement carefully considered designs for effective DM education.